Isolation And Structure Determination Of Bisdemthylaaptamine From Bunaken Marine Park Sponge Aaptos, sp. = lsolasi dan Penentuan Struktur Bisdemetilaaptamin dari Sepon Aaptos Sp. Taman Laut Bunaken - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Bisdemethylaaptamine, an alkaloid naphtyridine with molecular weight 200 and formulae molecule C111-18N202 has been isolated from Bunaken Marine Park sponge Aaptos sp. Isolation was done by using several stages of column chromatography and high performance liquid chromatography. Molecular weight of this naphtyridine alkaloid was determined by electron ionization (El) and electrospray ionization (ESI) mass spectroscopies and its structure assigned to be 8,9-dihydroxy-1H-benzold,e][1 , 6Jnaphtyridine by proton and carbon nuclear magnetic resonances (1H and 13C-NMR).